Combined Homeopathy and Allopathy Treatment for COVID-19: A Review (Bangladesh Journal of Infectious Diseases, 2020)
At the end of 2019, an outburst of a novel virus called severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was observed in Wuhan, China. World Health Organization proclaimed this upsurge as a Public Health Emergency of International Concern on 30th January 2020. In this article, epidemiology, the causative agent, pathogenesis of SARS-CoV-2 and its treatment approaches like homeopathy and allopathy are reviewed. However, our main focus was to collect and visualize some data which bring evidence that combined homeopathy and allopathy treatment can help to cure COVID-19.Bangladesh Journal of Infectious Diseases, October 2020;7(suppl_2):S38-S45